A star-shaped block copolymer for low-rank coal slurry and preparation method thereof
The star block copolymer dispersant prepared by RAFT controlled radical polymerization technology solves the problem of poor slurry performance of low-order coal, realizes the preparation of high-quality water coal slurry, has good fluidity and stability, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202310244947.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-14
AI Technical Summary
It is difficult to prepare high-quality water coal slurry in the prior art, especially when low-order coal is used. Due to the structural characteristics of low-order coal, traditional dispersants cannot effectively regulate the dispersant structure, resulting in poor slurry performance.
Using RAFT controlled radical polymerization technology, a star block copolymer dispersant with a highly controllable structure is prepared. By adjusting the number and structure of the dispersant, the electrostatic repulsion and steric resistance between coal particles are enhanced and coal aggregation is inhibited.
It improves the slurrying performance of low-order coal, enhances the fluidity and stability of water coal slurry, is suitable for large-scale production, and has good application prospects.
Smart Images

Figure CN116239735B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water-coal slurry dispersants and relates to a star-shaped block copolymer used for low-rank coal slurrying and a preparation method thereof. Background Art
[0002] Coal-water slurry is a coal-based slurry fuel, which is made by mixing about 60-70% coal by mass, 30-40% water and about 1% chemical additives (dispersants, stabilizers) evenly and then processed by physical processing. At present, the raw materials for making coal-water slurry are mainly bituminous coal with a high degree of coalification, but its reserves are relatively small and the price is high, which makes it difficult to meet the growing demand for slurry. Low-rank coal has a low price and abundant reserves in my country. The use of low-rank coal to prepare coal-water slurry has important practical significance for the rational use of low-rank coal, enriching and broadening the types of coal-water slurry, and enhancing the universality of coal-water slurry gasification technology. However, due to the large number of oxygen-containing functional groups on the surface of low-rank coal, high internal water, and poor pulping performance. Therefore, it is urgent to prepare low-rank coal into high-quality coal-water slurry.
[0003] Coal-water slurry dispersants can improve the interface structure and interaction of coal particles, reduce the bound water content in the slurry, and thus improve the performance of coal-water slurry. At present, the most common dispersants used for low-rank coal slurry are polycarboxylate dispersants, which are mostly prepared by traditional aqueous solution free radical copolymerization, resulting in a decrease in the regularity of the polymer chain, a disordered structure, and uncontrollable relative molecular mass, which is not conducive to the dispersion of low-rank coal and it is difficult to accurately control the dispersant structure according to the structural characteristics of the coal type.
[0004] Therefore, in view of the structural characteristics of low-rank coal, there is currently no efficient dispersant with an adjustable structure, which cannot meet the requirements for the slurrying performance of low-rank coal. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a star-shaped block copolymer for low-rank coal slurrying and a preparation method thereof, which adopts RAFT controlled radical polymerization, and can adjust the structure of the dispersant and the number of hydrophilic / hydrophobic groups according to the structural characteristics of the low-rank coal, enhance the electrostatic repulsion and steric hindrance between the coal particles, inhibit the aggregation of coal, and thus improve the slurrying performance of the low-rank coal.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A star-shaped block copolymer for low-rank coal slurry, wherein the star-shaped block copolymer has the structural formula:
[0008]
[0009] Wherein, m and n are the degree of polymerization, m=23-45, n=93-187.
[0010] A method for preparing a star-shaped block copolymer for low-rank coal slurry comprises the following steps:
[0011] S1, mixing tripotassium phosphate, 1-butanethiol, carbon disulfide and acetone, then heating to room temperature and keeping the temperature for 10 to 14 hours to obtain a mixed system a, adding 1,3,5-tri(bromomethyl)benzene to the mixed system a at -5 to 0°C, stirring, heating to room temperature and keeping the temperature for 12 to 13 hours, the heating and keeping the temperature are all carried out on the basis of stirring, to obtain a mixed system b, separating the product, and obtaining an intermediate product I;
[0012] S2, the intermediate product I, the initiator, styrene and dioxane are subjected to RAFT controlled radical polymerization reaction at 80-85° C. under vacuum, wherein the mass ratio of the intermediate product I to styrene is 1:(17-33), to obtain a mixed system C, and then unreacted monomers are removed to obtain M n =Intermediate product II of 10000 to 20000;
[0013] S3, the intermediate product II, the initiator, methoxy polyethylene glycol acrylate and dioxane are subjected to RAFT controlled radical polymerization reaction at 80-85° C. under vacuum, wherein the mass ratio of the intermediate product II to the methoxy polyethylene glycol acrylate is 1:(1-3), to obtain a mixed system d, and then unreacted monomers are removed to obtain M n =20000~40000 star-shaped block copolymer for low-rank coal slurry.
[0014] Preferably, S1 first mixes tripotassium phosphate, 1-butanethiol, carbon disulfide and acetone at -5 to 0°C, stirs, and then heats and keeps warm, wherein the heating and keeping warm are both carried out on the basis of stirring, to obtain a mixed system a.
[0015] Furthermore, the molar ratio of the 1,3,5-tris(bromomethyl)benzene, tripotassium phosphate, 1-butanethiol and carbon disulfide is 1:2:2:6, and the mass of acetone is 2 to 8 times the total mass of tripotassium phosphate, 1-butanethiol and carbon disulfide.
[0016] Preferably, the initiator described in S2 and S3 is azobisisobutyronitrile or azobisisoheptanenitrile.
[0017] Preferably, in S2, the initiator is 3% of the mass of styrene, and the dioxane is twice the total mass of styrene and the intermediate product I.
[0018] Preferably, unreacted monomers are removed in S2 by the following process:
[0019] The mixed system c is immersed in methanol, and the unreacted monomers are precipitated, and then filtered to obtain the intermediate product II;
[0020] In S3, unreacted monomers are removed by the following process:
[0021] The mixed system d is immersed in methanol, and the unreacted monomers are precipitated, and then filtered to obtain the star-shaped block copolymer.
[0022] Preferably, in S3, the initiator is 3% of the mass of methoxy polyethylene glycol acrylate, and the dioxane is 2 times the total mass of methoxy polyethylene glycol acrylate and intermediate product II.
[0023] Preferably, the free radical polymerization reactions described in S2 and S3 are both carried out for 24-25 hours.
[0024] A star-shaped block copolymer for low-rank coal slurrying obtained by any one of the above-mentioned methods for preparing a star-shaped block copolymer for low-rank coal slurrying.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The invention discloses a method for preparing a star-shaped block copolymer for low-rank coal slurry, wherein 1,3,5-tri(bromomethyl)benzene, tripotassium phosphate, 1-butyl mercaptan, carbon disulfide and acetone are firstly used to prepare a chain transfer agent required for polymerization through a substitution reaction, and then RAFT controlled free radical polymerization is performed to prepare M by combining an initiator, styrene and dioxane. n =10000~20000 intermediate product, and finally combine initiator, methoxy polyethylene glycol acrylate and dioxane to prepare M with styrene as hydrophobic group and methoxy polyethylene glycol acrylate as hydrophilic group n =20000~40000 dispersant star block copolymer. The relative molecular weight and structural height of the dispersant are controllable, and the number of hydrophilic / hydrophobic groups is adjustable. Therefore, the structure of the dispersant and the number of hydrophilic / hydrophobic groups can be adjusted according to the structural characteristics of low-rank coal, the electrostatic repulsion and steric hindrance between coal particles can be enhanced, coal aggregation can be inhibited, and thus the slurrying performance of low-rank coal can be improved. The synthesis method of the present invention has a simple preparation process, can be used for the preparation of low-rank coal water slurry, has excellent dispersing ability, is suitable for large-scale production, is of great significance for improving energy utilization and enriching the types of water-coal slurries, and has good application prospects.
[0027] The star-shaped block copolymer of the present invention has the advantage that compared with conventional polymer dispersants, the star-shaped block copolymer dispersant has a more regular molecular structure; conventional polymer dispersants mostly adopt random copolymerization, and the relative molecular mass of the obtained polymer cannot be controlled. The present invention uses RAFT controlled radical polymerization to achieve precise regulation of the relative molecular mass of the copolymer and the content and ratio of hydrophilic and hydrophobic groups; and can change the structure of the copolymer and the type and length of the hydrophilic and hydrophobic segments according to the structural characteristics of different low-rank coals, so as to prepare high-efficiency dispersants for different types of coal. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a synthetic route diagram of the star-shaped block copolymer dispersant of the present invention;
[0029] Figure 2 is the hydrogen nuclear magnetic resonance spectrum of Example 1;
[0030] Figure 3 This is a comparison chart of the viscosity reduction effect of the dispersant star-shaped block copolymer prepared in Example 5 and the existing dispersant sodium lignin sulfonate on lignite water-coal slurry. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0032] The present invention provides a method for preparing a star-shaped block copolymer as a dispersant for low-rank coal slurry, such as Figure 1 As shown, the following steps are included:
[0033] S1: Under -5 to 0°C, tripotassium phosphate, 1-butanethiol, carbon disulfide and acetone are mixed, the amount of acetone is 2 to 8 times the total mass of the above tripotassium phosphate, 1-butanethiol and carbon disulfide, and stirred for 1 to 1.5 hours, and the mixture is heated to room temperature and stirred for 10 to 14 hours. Then it is cooled to -5 to 0°C, 1,3,5-tri(bromomethyl)benzene is added dropwise and stirred for 1 to 1.5 hours, and the molar ratio of 1,3,5-tri(bromomethyl)benzene, tripotassium phosphate, 1-butanethiol and carbon disulfide is 1:2:2:6, and finally heated to room temperature and continued to stir for 12 to 13 hours, and rotary evaporated at 45°C for 30 minutes to obtain intermediate product I.
[0034]
[0035] S2: The intermediate product I, initiator, styrene and dioxane are added to the reaction bottle in sequence, the amount of initiator is 3% of the mass of styrene, the mass ratio of the intermediate product I to styrene is 1:(17-33), the amount of dioxane is 2 times the total mass of styrene and the intermediate product I, the reaction is evacuated to a vacuum state, and the reaction is stirred in an oil bath at 80-85°C for 24-25h. After the reaction is completed, the unreacted monomer is removed by reprecipitation to obtain M n =Intermediate product II of 10000~20000.
[0036]
[0037] S3: Add intermediate product II, initiator, methoxy polyethylene glycol acrylate and dioxane to the reaction bottle in sequence, the polymerization degree of methoxy polyethylene glycol acrylate is 9, the amount of initiator is 3% of the mass of methoxy polyethylene glycol acrylate; the mass ratio of intermediate product II to methoxy polyethylene glycol acrylate is 1:(1-3), the amount of dioxane is 2 times the total mass of methoxy polyethylene glycol acrylate and intermediate product II, evacuate to vacuum state, place it in an oil bath at 80-85°C and stir for reaction for 24-25h, remove unreacted monomers by reprecipitation after the reaction is completed, and obtain the number average molecular weight M n = Star-shaped block copolymer dispersant with a molecular weight of 20,000 to 40,000.
[0038] The initiators of S2 and S3 are azobisisobutyronitrile (AIBN) or azobisisoheptanenitrile (ABVN). The reprecipitation method is to pour the corresponding mixture into a beaker filled with excess methanol, so that the unreacted monomer will settle, and the unreacted residual monomer can be removed by filtration. The reaction bottle is a Schlenk flask, and the vacuum condition is achieved by placing all reagents in the Schlenk flask and degassing through three freeze-thaw cycles.
[0039] In S2, the mass ratio of intermediate product I to styrene is given by the formula:
[0040]
[0041] Bring in M n中间产物Ⅱ =10000~20000 can be calculated.
[0042] In S3, the mass ratio of intermediate II to methoxy polyethylene glycol acrylate is given by the formula:
[0043]
[0044] Bring in M n产物 =20000~40000 can be calculated.
[0045] The copolymer dispersant structural formula is:
[0046]
[0047] Among them, m and n are the degree of polymerization, m ranges from 23 to 45, and n ranges from 93 to 187. Polystyrene is a hydrophobic group that contacts the surface of low-rank coal, and polymethoxy polyethylene glycol acrylate is a hydrophilic group that contacts water.
[0048] Example 1
[0049] At 0°C, 14.9 g of tripotassium phosphate, 7.6 ml of 1-butanethiol, 12.6 ml of carbon disulfide and 150 ml of acetone were mixed evenly and stirred for 1 hour. The mixture was heated to room temperature and stirred for 12 hours. Then the mixture was cooled to 0°C, 7.14 g of 1,3,5-tri(bromomethyl)benzene was added dropwise and stirred for 1 hour. Finally, the mixture was heated to room temperature and stirred for 12 hours. After rotary evaporation at 45°C for 30 minutes, intermediate product I was obtained.
[0050] 540 mg of intermediate product I, 180 mg of initiator AIBN, 9.2 g of styrene and 9.6 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers to obtain M n =Intermediate II of 10000.
[0051] 1500 mg of intermediate product II, 60 mg of initiator AIBN, 1.5 g of methoxy polyethylene glycol acrylate and 3 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, and M was obtained. n =20000 dispersant star block copolymer.
[0052] Example 2
[0053] At 0°C, 14.9 g of tripotassium phosphate, 7.6 ml of 1-butanethiol, 12.6 ml of carbon disulfide and 150 ml of acetone were mixed evenly and stirred for 1 hour. The mixture was heated to room temperature and stirred for 12 hours. Then the mixture was cooled to 0°C, 7.14 g of 1,3,5-tri(bromomethyl)benzene was added dropwise and stirred for 1 hour. Finally, the mixture was heated to room temperature and stirred for 12 hours. After rotary evaporation at 45°C for 30 minutes, intermediate product I was obtained.
[0054] 360 mg of intermediate product I, 180 mg of initiator ABVN, 9 g of styrene and 9.3 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining M n =Intermediate II of 15000.
[0055] 1500 mg of intermediate product II, 60 mg of initiator ABVN, 1.5 g of methoxy polyethylene glycol acrylate and 3 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining M n =30000 dispersant star block copolymer.
[0056] Example 3
[0057] At 0°C, 14.9 g of tripotassium phosphate, 7.6 ml of 1-butanethiol, 12.6 ml of carbon disulfide and 150 ml of acetone were mixed evenly and stirred for 1 hour. The mixture was heated to room temperature and stirred for 12 hours. Then the mixture was cooled to 0°C, 7.14 g of 1,3,5-tri(bromomethyl)benzene was added dropwise and stirred for 1 hour. Finally, the mixture was heated to room temperature and stirred for 12 hours. After rotary evaporation at 45°C for 30 minutes, intermediate product I was obtained.
[0058] 270 mg of intermediate product I, 180 mg of initiator ABVN, 9 g of styrene and 9.3 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining M n =Intermediate II of 20000.
[0059] 1500 mg of intermediate product II, 60 mg of initiator ABVN, 1.5 g of methoxy polyethylene glycol acrylate and 3 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining M n =40000 dispersant star block copolymer.
[0060] Example 4
[0061] At 0°C, 14.9 g of tripotassium phosphate, 7.6 ml of 1-butanethiol, 12.6 ml of carbon disulfide and 150 ml of acetone were mixed evenly and stirred for 1 hour. The mixture was heated to room temperature and stirred for 12 hours. Then the mixture was cooled to 0°C, 7.14 g of 1,3,5-tri(bromomethyl)benzene was added dropwise and stirred for 1 hour. Finally, the mixture was heated to room temperature and stirred for 12 hours. After rotary evaporation at 45°C for 30 minutes, intermediate product I was obtained.
[0062] 360 mg of intermediate product I, 180 mg of initiator AIBN, 9 g of styrene and 9.3 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining M n =Intermediate II of 15000.
[0063] 1500 mg of intermediate product II, 25 mg of initiator AIBN, 0.5 g of methoxy polyethylene glycol acrylate and 2 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining a hydrophilic group to hydrophobic group mass ratio of 1:3 and M n =20000 dispersant star block copolymer.
[0064] Example 5
[0065] At 0°C, 14.9 g of tripotassium phosphate, 7.6 ml of 1-butanethiol, 12.6 ml of carbon disulfide and 150 ml of acetone were mixed evenly and stirred for 1 hour. The mixture was heated to room temperature and stirred for 12 hours. Then the mixture was cooled to 0°C, 7.14 g of 1,3,5-tri(bromomethyl)benzene was added dropwise and stirred for 1 hour. Finally, the mixture was heated to room temperature and stirred for 12 hours. After rotary evaporation at 45°C for 30 minutes, intermediate product I was obtained.
[0066] 320 mg of intermediate product I, 60 mg of initiator AIBN, 2.65 g of styrene and 3 g of dioxane were added to the reaction bottle in sequence, and the reaction was evacuated to a vacuum state. The reaction bottle was placed in an 80°C oil bath and stirred for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining M n =Intermediate II of 5000.
[0067] 560 mg of intermediate product II, 60 mg of initiator AIBN, 1.5 g of methoxy polyethylene glycol acrylate and 2.1 g of dioxane were added to the reaction bottle in sequence, evacuated to a vacuum state, placed in an 80°C oil bath and stirred for reaction for 24 h. After the reaction was completed, the mixture was poured into a beaker containing a large amount of methanol for reprecipitation to remove unreacted monomers, thereby obtaining a hydrophilic group to hydrophobic group mass ratio of 3:1 and M n =20000 dispersant star block copolymer.
[0068] Performance Characterization
[0069] Structural characterization:
[0070] In order to characterize the structure and conversion rate of the star-shaped block copolymer, taking Example 1 as an example, the dispersant prepared in Example 1 was characterized by nuclear magnetic resonance hydrogen spectrum. The results are as follows: Figure 2 shown.
[0071] Depend on Figure 2 It can be seen that the peaks at 7.25-6.82 ppm chemical shift are hydrogens in different chemical environments in the benzene ring, which is consistent with the intermediate Ⅰ 1 H NMR spectrum Figure 1 However, the peaks of hydrogen in different chemical environments on the -CH=CH2 group of the methoxy polyethylene glycol acrylate molecular structure (at 6.76, 5.89 and 5.33 ppm chemical shifts) in the polymer spectrum were weakened; while the peak belonging to -CH2- appeared within the 1.73 ppm shift range, indicating the breakage of the C=C bond, proving that PEGMA and intermediate product I have been copolymerized, and a star-shaped block copolymer has been successfully prepared with a conversion rate of 92.3%. The conversion rate is calculated by the ratio of the area of the peaks of hydrogen in different chemical environments on the -CH=CH2 group to the peak of -CH2-.
[0072] The relative molecular mass of the star-shaped block copolymer is used to characterize whether the preparation process is controllable. The relative molecular mass of the star-shaped block copolymer is measured by Agilent 1260 InfinityⅡ gel chromatography. The measurement results are shown in Table 1.
[0073] Table 1 Number average molecular weight and conversion rate of each example
[0074]
[0075] As shown in Table 1, the relative molecular weight of the block copolymers prepared in each embodiment is basically consistent with the expected relative molecular weight, and the conversion rate is about 90%, indicating that the controllable preparation of the star-shaped block copolymers has been successfully achieved. And the number average molecular weight of each embodiment can prove that the type of initiator in this scheme has little effect on the relative molecular weight of the polymer.
[0076] Performance Testing:
[0077] In order to characterize the dispersing effect of the star-shaped block copolymer used as a dispersant for low-rank coal slurry on Inner Mongolia lignite water-coal slurry, the slurry concentration was fixed at 55wt%, the dispersant dosage was 0.5wt%, and the slurry apparent viscosity was measured using a NXS-4C rotational viscometer from Chengdu Instrument Factory, and its flow properties were observed. The measurement results are shown in Table 2.
[0078] In order to characterize the stabilizing effect of the dispersant star-shaped block copolymer of the present invention on the water-coal slurry of Inner Mongolia lignite, the water-coal slurry obtained by using the star-shaped block copolymer prepared in Examples 1 to 5 using the above-mentioned dosage and method was stirred and poured into a 100mL measuring cylinder (3cm in diameter), and then the measuring cylinder mouth was sealed and placed at room temperature for 3 days, and the upper clear liquid of the slurry in the measuring cylinder was sucked out by a syringe and weighed, recorded as m1, and the mass of the upper clear liquid and the total mass of the slurry (m0) were the ratio of the water separation rate. The calculation of the water separation rate was calculated using the following formula, water separation rate (wt%) = m1 / m0×100%, and the water separation rate measurement results are shown in Table 2.
[0079] Table 2 Performance test results of various embodiments
[0080]
[0081] As shown in Table 2, from Example 1 to Example 3, as the relative molecular weight of the star-shaped block copolymer gradually increases, the apparent viscosity of the prepared Inner Mongolia lignite water-coal slurry gradually increases, and the relative molecular weight of the dispersant suitable for Inner Mongolia lignite slurry is M n = 20000. Under the condition of the optimal relative molecular mass, the ratio of the hydrophilic and hydrophobic groups in the polymer is adjusted, and the apparent viscosity of the coal-water slurry prepared in Example 5 with mainly hydrophilic groups is significantly lower than the apparent viscosity of the coal-water slurry prepared in Example 4 with mainly hydrophobic groups.
[0082] From the results in Table 2, it can be seen that from Example 1 to Example 3, as the relative molecular mass of the star-shaped block copolymer gradually increases, the water separation rate of the prepared Inner Mongolia lignite water-coal slurry gradually increases, and the relative molecular mass of the dispersant suitable for Inner Mongolia lignite slurry is Mn=20000. Under the condition of the optimal relative molecular mass, the ratio of the hydrophilic and hydrophobic groups in the polymer is adjusted, and the water separation rate of the water-coal slurry prepared in Example 5, which is mainly composed of hydrophilic groups, is significantly lower than the water separation rate of the water-coal slurry prepared in Example 4, which is mainly composed of hydrophobic groups. Combined with the apparent viscosity of the water-coal slurry, it can be concluded that the mass ratio of the hydrophilic group to the hydrophobic group prepared in Example 5 is 3:1 and M n =20000 block copolymer dispersant has good dispersibility and can improve the stability of water-coal slurry. It is a good dispersant suitable for Inner Mongolia lignite.
[0083] The dispersant prepared in Example 5 was compared with the traditional sodium lignin sulfonate dispersant. The results of the change of the apparent viscosity of the slurry with the shear rate are as follows: Figure 3 shown.
[0084] from Figure 3 It can be seen that when the dispersant prepared in Example 5 is used, the apparent viscosity of the Inner Mongolia lignite water-coal slurry first decreases and then tends to be flat as the shear rate increases, showing pseudoplastic fluid characteristics. -1 When the apparent viscosity of the Inner Mongolia lignite water-coal slurry prepared in Example 5 drops to 653 mPa·s, that is, the viscosity corresponding to Example 5 in Table 2 is significantly lower than that of the lignite water-coal slurry prepared with the sodium lignin sulfonate dispersant.
[0085] In summary, the star-shaped polymer block copolymer dispersant for low-rank coal slurrying of the present invention can adjust the ratio of its hydrophilic and hydrophobic groups according to the structural characteristics of Inner Mongolia lignite due to its controllable relative molecular mass and structure, thereby achieving the purpose of improving the fluidity, dispersion stability and slurrying concentration of water-coal slurry, which is of great significance for improving energy utilization and enriching the types of water-coal slurries.
[0086] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A star-shaped block copolymer for low-rank coal slurrying, characterized in that: The star-shaped block copolymer structural formula is: Wherein, m and n are the degree of polymerization, m=23-45, n=93-187.
2. A method for preparing a star-shaped block copolymer for low-rank coal slurry, characterized in that: The steps include: S1, tripotassium phosphate, 1-butanethiol, carbon disulfide and acetone are mixed uniformly, then heated to room temperature and kept warm for 10 to 14 hours to obtain a mixed system a, 1,3,5-tri(bromomethyl)benzene is added to the mixed system a at -5 to 0°C, and then stirred, heated to room temperature and kept warm for 12 to 13 hours, the heating and keeping warm are all carried out on the basis of stirring, to obtain a mixed system b, and the product is separated to obtain an intermediate product I; S2, the intermediate product I, the initiator, styrene and dioxane are subjected to RAFT controlled radical polymerization reaction at 80-85° C. under vacuum, wherein the mass ratio of the intermediate product I to styrene is 1:(17-33), to obtain a mixed system C, and then unreacted monomers are removed to obtain M n =Intermediate product II of 10000 to 20000; S3, the intermediate product II, the initiator, methoxy polyethylene glycol acrylate and dioxane are subjected to RAFT controlled radical polymerization reaction at 80-85° C. under vacuum, wherein the mass ratio of the intermediate product II to the methoxy polyethylene glycol acrylate is 1:(1-3), to obtain a mixed system d, and then unreacted monomers are removed to obtain M n =20000~40000 star-shaped block copolymer for low-rank coal slurry.
3. The method for preparing a star-shaped block copolymer for low-rank coal slurry according to claim 2, characterized in that: S1: firstly, tripotassium phosphate, 1-butanethiol, carbon disulfide and acetone are mixed at -5 to 0°C, stirred, and then heated and kept warm. The heating and keeping warm are both carried out on the basis of stirring to obtain a mixed system a.
4. The method for preparing a star-shaped block copolymer for low-rank coal slurry according to claim 3, characterized in that: The molar ratio of the 1,3,5-tris(bromomethyl)benzene, tripotassium phosphate, 1-butanethiol and carbon disulfide is 1:2:2:6, and the mass of acetone is 2 to 8 times the total mass of tripotassium phosphate, 1-butanethiol and carbon disulfide.
5. The method for preparing a star-shaped block copolymer for low-rank coal slurry according to claim 2, characterized in that: The initiator described in S2 and S3 is azobisisobutyronitrile or azobisisoheptanenitrile.
6. The method for preparing a star-shaped block copolymer for low-rank coal slurry according to claim 2, characterized in that: In S2, the initiator is 3% of the mass of styrene, and the dioxane is twice the total mass of styrene and the intermediate product I.
7. The method for preparing a star-shaped block copolymer for low-rank coal slurry according to claim 2, characterized in that: In S2, unreacted monomers are removed by the following process: The mixed system c is immersed in methanol, and the unreacted monomers are precipitated, and then filtered to obtain the intermediate product II; In S3, unreacted monomers are removed by the following process: The mixed system d is immersed in methanol, and the unreacted monomers are precipitated, and then filtered to obtain the star-shaped block copolymer.
8. The method for preparing a star-shaped block copolymer for low-rank coal slurry according to claim 2, characterized in that: In S3, the initiator is 3% of the mass of methoxy polyethylene glycol acrylate, and the dioxane is twice the total mass of methoxy polyethylene glycol acrylate and intermediate product II.
9. The method for preparing a star-shaped block copolymer for low-rank coal slurry according to claim 2, characterized in that: The free radical polymerization reactions described in S2 and S3 are both carried out for 24 to 25 hours.
10. A star-shaped block copolymer for low-rank coal slurrying obtained by the preparation method of the star-shaped block copolymer for low-rank coal slurrying according to any one of claims 2 to 9.